Media surface properties and the development of nitrifying biofilms in mixed cultures for wastewater treatment - Stephenson, Tom; Reid, E.; Avery, L. M.; Jefferson, Bruce (Institute of Chemical Engineers, 2013)
Plastic was tested to select biofilm support media that would enhance nitrification in the presence of heterotrophs. Eight different types (acrylonitrile butadiene styrene, nylon, polycarbonate, polyethylene, polypropylene, polytetraflouroethylene (PTFE), polyvinyl chloride and tufnol) were immersed in an aerobic fed-batch reactor receiving domestic settled wastewater. Nitrification rates did not correlate with biomass concentrations, nor surface roughness of the plastics as measured by atomic force microscopy (AFM). The maximum nitrification rate of 1.5 g/m2d1 was obtained from biofilms growing on PTFE which had the lowest surface adhesion force (8nN). Nitrification rates for the biofilms were inversely correlated with the attraction forces as measured by the AFM.